Academic Senate Minutes 2010-10-14 - Academic Senate:::::::::
Chair Report. Agenda – approved. Minutes of 9/16/10 – deferred. Revision to the Global Studies minor – approved. President Report. Special Report: Senate Representatives to the Core Implementation Group of the Graduation Initiative. Resolution from SAC: Endorse letter to Vice President of SAEM regarding a Student Advocate approved. CFA Report. Revision to the Learning Objectives for Areas A and C – postponed to next Senate meeting. Revision to the GE Unit Policy - postponed to 12/9 to allow the GE Subcommittee to develop a clear set of methodologies as to how they are going to determine there are a sufficient number of three units GE courses in a given area.